2013
DOI: 10.9790/2402-0462224
|View full text |Cite
|
Sign up to set email alerts
|

Development and Analysis of Blended Pineapple-Watermelon Ready To Drink (RTD) Juice.

Abstract: Abstract:The physicochemical properties of juice from pineapple and watermelon and their ready to drink (RTD) blends were carried out. The % watermelon juice and pineapple juice of each formulation (v/v) were BL1 (70:30), BL2 (60:40), BL3 (50:50), BL4 (30:70) and BL5 (40:60). The standards were done without blending the two juices SPJ (100% standard pineapple juice) and SWJ (100% standard watermelon juice). The results of the analysis of Vitamin C content (mg/g) gave 125.26 in SWJ, 38.90 in SPJ, 111.58 in BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…Similar types of results were also reported by Oyeleke et al, (2013). It indicated that the titrable acidity increases as the addition of pineapple juice to the watermelon increases during storage period.…”
Section: Acidity (%)supporting
confidence: 87%
“…Similar types of results were also reported by Oyeleke et al, (2013). It indicated that the titrable acidity increases as the addition of pineapple juice to the watermelon increases during storage period.…”
Section: Acidity (%)supporting
confidence: 87%
“…Igbabul et al [22] where a significant (P<0.05) increase was observed in the produced cookies. Samia et al [23], Oyeleke et al [24], Cláudia et al [25] and Makanjuola and Makanjuola [26] also reported high ash contents that are similalr to this present study. The results obtained in this study are also in agreement with similar reports by Bhosale and Udachan [27], Olorode et al [28] who also expressed similar ranged of ash contents.…”
Section: Proximate Composition Of Cookies From Wheat Trifoliate Yam A...supporting
confidence: 84%
“…A higher concentration (5.0 ml) of lemon juice in the beverage might be contributing to acidity which may result in its decreased acceptability. The OAA of juices is greatly influenced by TSS: acid and their suitable ratio are very important for the acceptability of juices [29,30].…”
Section: Effect On Overall Acceptabilitymentioning
confidence: 99%